2020
DOI: 10.2478/s11686-020-00174-6
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of Cutaneous Leishmaniasis in Sri Lanka and Identification of Existing Knowledge Gaps

Abstract: Purpose Sri Lanka is endemic to cutaneous leishmaniasis and reported as the latest focus of leishmaniasis in the Asian subcontinent. Annually, the number of leishmaniasis cases is increasing; therefore, more efficient diagnostic tools, treatment methods and effective prevention measures are indispensable. For this reason, many studies were conducted regarding leishmaniasis infections in Sri Lanka; however, some areas need more attention. Thus, in this review, we comprehensively discussed the studies on leishma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 65 publications
(128 reference statements)
0
21
0
2
Order By: Relevance
“…A study carried out to analyse epidemiological data showed that almost 90% of the leishmaniasis cases reported between 2009 and 2016 were from Anuradhapura, Hambantota, Polonnaruwa, Kurunegala, and Matara as endemic districts [4]. This research is the first preliminary study that has been carried out to determine the composition, abundance, flight range and peak active times of sand fly species in an endemic focus of leishmaniasis in Kurunegala District.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…A study carried out to analyse epidemiological data showed that almost 90% of the leishmaniasis cases reported between 2009 and 2016 were from Anuradhapura, Hambantota, Polonnaruwa, Kurunegala, and Matara as endemic districts [4]. This research is the first preliminary study that has been carried out to determine the composition, abundance, flight range and peak active times of sand fly species in an endemic focus of leishmaniasis in Kurunegala District.…”
Section: Discussionmentioning
confidence: 88%
“…Phlebotomus argentipes Annandale and Brunetti (Diptera: Psychodidae) are the major vectors of VL (kala-azar) in India [3]. The predominant sand fly species in Sri Lanka is also Phlebotomus argentipes [4].…”
Section: Introductionmentioning
confidence: 99%
“…Annually, the number of reported CL cases has been increasing since this time. Cases have been reported from many districts in the country mainly from Anuradhapura, Polonnaruwa, Hambantota, Kurunegala, and Matara [2]. According to reports in 2019 alone, 3271 cases were reported across the country [7].…”
Section: Notification Of Leishmaniasismentioning
confidence: 99%
“…Effective surveillance systems provide essential information to take timely and appropriate actions for disease control and prevention, and to manage public health-care policies and programs [1]. Leishmaniasis was declared as a notifiable disease in Sri Lanka in 2008 and annually an increasing number of cases have been reported from many districts in the country [2]. In this paper, we present a comprehensive compilation and critique of the disease notification pathway for leishmaniasis and the current status of leishmaniasis reporting in Sri Lanka, while discussing how the routine communicable disease surveillance system has assisted in the increased case detection of leishmaniasis in the country.…”
Section: Introductionmentioning
confidence: 99%
“…A more recent survey among 668 dogs in 18 out of 25 districts in Sri Lanka revealed a Leishmania amastigote prevalence of only 0.9% (2/668) in blood [ 9 ]. These findings suggest the possibility of dogs acting as reservoir hosts [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%